(3GdhSjWs - (3GdSQNSj , eMeO Hf eMeO Hf eMeO, QVj GdOjf GdSQNSj,J (B571 (3g` s
(3ChdgG (B:s
(3jHJOF HGdCVMjI s
(3BNQgG (B:s
(3jfJgi HUdM GdecGJH ai HGH GdUdM s
(3ef GdfSNI faSgGs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B24 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B278s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B9 - (3U (B277 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B2008s
Keywords: (3Gdabg GdMfajs